(untitled) (Bangladesh Medical Journal, 2010)
Hypertension is a silent killer. Bangladeshis are racially predisposed to cardiovascular disease, and the increasing burden of hypertension has only added to the problem. Economic constraints and the allure of additional benefits without adverse effects have made lifestyle modifications an attractive proposition in developing and developed countries alike. Blood pressure is a continuum and any increase above optimum level confers additional independent risk of cardiovascular disease. We review screening, diagnosis and management using lifestyle measures and pharmacotherapy. We then discuss the barriers and challenges to implementing this approach and what can be done regarding prevention, screening, lifestyle modification and pharmacotherapy in our country. By adopting a comprehensive population based approach including policy level interventions directed at promoting lifestyle changes; a healthy diet (appropriate calories, low in saturated fats and salt and rich in fruits and vegetables), increased physical activity, and a smoking free society, properly balanced with a high risk approach of cost effective clinical care, Bangladesh can effectively control hypertension and improve public health. DOI: 10.3329/bmj.v39i1.6232 Bangladesh Medical Journal 2010; 39(1): 40-43